TOTALLY M*-PARANOORMAL OPERATORS - Ahmed, Buthainah A; Nassir, Sadiq Naji (Al-Nahrain Journal of Science, 2018)
In this paper we introduce a class of operators on a Hilbert space, we call the elements of this class totally M*-paranormal operator.We study some basic properties of these operators and we give some sufficient conditions for a totally M*-paranormal operator to be normal operator.